Optical Fiber Communication Conference/National Fiber Optic Engineers Conference 2013 2013
DOI: 10.1364/ofc.2013.ow4a.3
|View full text |Cite
|
Sign up to set email alerts
|

Intersymbol Interference Penalties for OOK and 4-PAM in Short-range Optical Communications

Abstract: Intersymbol interference penalties of OOK and 4-PAM were compared in the context of short-range optical links with directly modulated VCSELs. The maximum achieved bit rate with 4-PAM was 38 Gbps and 32 Gbps with OOK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Multilevel modulation such as four‐level pulse amplitude modulation (PAM) has the potential to increase throughput in a given bandwidth, at the cost of 3.3 dB worse sensitivity than OOK at the same bit rate [4]. An additional benefit of 4‐PAM is that compared with OOK at the same bit rate, the symbol rate is reduced by half, which reduces the effects of intersymbol interference [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multilevel modulation such as four‐level pulse amplitude modulation (PAM) has the potential to increase throughput in a given bandwidth, at the cost of 3.3 dB worse sensitivity than OOK at the same bit rate [4]. An additional benefit of 4‐PAM is that compared with OOK at the same bit rate, the symbol rate is reduced by half, which reduces the effects of intersymbol interference [4].…”
Section: Introductionmentioning
confidence: 99%
“…The fastest reported link bit rate to date is 56.1 Gbits [3], which was demonstrated in a VCSEL-based link using on-off keying (OOK) with predistortion and a specially developed driver circuit to match the VCSEL. Multilevel modulation such as four-level pulse amplitude modulation (PAM) has the potential to increase throughput in a given bandwidth, at the cost of 3.3 dB worse sensitivity than OOK at the same bit rate [4]. An additional benefit of 4-PAM is that compared with OOK at the same bit rate, the symbol rate is reduced by half, which reduces the effects of intersymbol interference [4].…”
mentioning
confidence: 99%
“…Investigation of the performance of 4-PAM under ISI, [21][22][23] has shown that at a fixed symbol rate and channel rise time the ISI penalty for 4-PAM is twice as large as for OOK. Fig.…”
Section: Data Transmission With 4-pam and Vcselsmentioning
confidence: 99%
“…In high speed, low distance and low power application where the attenuation in the fibre is negligible and high bandwidth needs to be reached, 4‐PAM represent an advantageous alternative to OOK. Nevertheless, increasing the DR of OOK causes an ISI power penalty increase and the ISI penalty of OOK exceeds the power penalty of M‐PAM [10].…”
Section: ‐Pam Modulationmentioning
confidence: 99%